Perancangan Alat Pemotong Pelat Otomatis Dengan Las Oxy-Acetylene - Gilang Syukma Pratama; Herisiswanto Herisiswanto; Dedi Rosa Putra Cupu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Currently the most widely used cutting steel is cutting with oxygen gas, the manual weld cutting makes the cutting result of less appropriate as well as the complicated process. The cutting tool plate is made to facilitate the work especially in the field of construction. In this research aims to design the Oxy-Acetylene automatic plate cutting tool that makes easier of the plate cutting process. In the design process used the Autodesk Inventor 2015 software as well as analysis of structural strength in this design. From the design process, was obtained the output in the form of technical drawings of the automatic plate cutting of Oxy-Acetylene.The analysis process was done in two ways with manual calculations and using Autodesk Inventor 2015. Then from the calculation results were obtained the voltage that occurs on the axis y = 0.908 MPa on the x-axis 0.7334 MPa the deflection occurring on the y-axis = 0.001868 mm and on the axis x = 0.002798 mm. Keywords : Automatic plate cutting machines, stress, deformation, Oxy-Acetylene